Internalizing externalities of loss-prevention through insurance monopoly: An analysis of interdependent risks - Annette Hofmann (Hamburg University, Institute for Risk and Insurance, 2005)
When risks are interdependent, loss-prevention activities of one agent influence the risks faced by others. The social return to an investment in loss-prevention is greater than the private return. From a perspective of social welfare, the market allocation is not optimal and leads to under-investment in prevention allround. This article considers consumer welfare under conditions of interdependent risks and demonstrates that a monopolistic insurer can internalize the arising externalities by setting appropriate prevention incentives through insurance premiums. A monopoly insurance solution reduces not only costs of risk selection, but can also play an important role in loss-prevention.
Keywords: C70; D62; G22; 330; externalities; insurance monopoly; Nash equilibrium; social welfare